Storage assignment and order batching problem in Kiva mobile fulfilment system. Issue 11 (2nd November 2018) - Xiang, Xi; Liu, Changchun; Miao, Lixin
ABSTRACT: This article studies the storage assignment and order batching problem in the Kiva mobile fulfilment system. The storage assignment model aims to decide which product to put in which pod to maximize the product similarity and the order batching model aims to minimize the number of visits of pods. To solve the order batching problem, a heuristic is proposed, where a batch schedule is initialized with the objective of maximizing the order association or minimizing order alienation and improved by variable neighbourhood search. Computational experiments are conducted to verify the performance of the proposed model and algorithm.